Monitoramento estrutural baseado na técnica de ondas Lamb para detecção de falhas em estruturas metálicas parafusadas - Silva Junior, Anorosval Pedro Leirias da (2017)
This work aims at the study and application of a method of monitoring the integrity of a metal structure based on Lamb waves. For monitoring piezoelectric pads are used, in function on your low monetary cost. The pellets are used as actuators and receivers using the property of piezoelectric materials that associates the electrical impedance with mechanical impedance. The analysis part of the creation of a sign consisting of an electrical pulse in the Lamb waves and your format application in a piezoelectric structure mounted insert in study, causing a vibration that propagate along the structural element. Follows on the uptake of this vibration for piezoelectric other pad also coupled to the structure that converts it into a signal and terminates in the interpretation of this signal. The Lamb wave that generates the excitation pulse sent to the piezoelectric element is a Wavelet function. The structure is monitored in your healthy state and in your damaged state. Based on studies of vibration and use of Continuous Wavelet transform, compare the readings of signals obtained in trials conducted in full structure then the structure damaged. Using a metric that correlates these readings, defined as Damage index, the method detects the existence of damage to the structure. Three experiments are performed. The experiments consisting in the analysis of a structure formed by a single metal beam where actuators and receptors are disposed in various positions. Was inserted a screw in your Constitution, with the function to simulate the damage. The structure containing the screw configures your healthy state and when the bolt is removed from the structure, has been damaged. The results of the tests allow the qualitative evaluation of the discovery, on the basis of distance on the position of the damage. Also uses an accelerometer as a receiver, in order to obtain a comparison factor to the results obtained. Due to the amount of observed data was using a statistical summary measures treatment and dispersions for the analysis. It is concluded that the methodology presented using Lamb wave technique in conjunction with the application of the index of damage produces satisfactory results, and can be used as an alternative in the interpretation of signs where the goal is the detection of damage, Since the methodology was able to indicate the existence of damage regardless of your position in the proposed structure.